Surface Plasmon Resonance for the Interaction of Capsular Polysaccharide (CPS) With KpACE - Zhe Wang; Lijun Wang; Xiaomin Zhang; Jing- Zhang; Chao Cai (Bio-Protocol)
The study of carbohydrate–protein interactions is crucial for clarifying biological processes and identifying potential drug candidates. However, due to the complex structure of carbohydrates, such as high molecular weight, dynamic flexibility, and high solution viscosity, it is challenging to study their interactions with diverse proteins. Conventional analytical techniques like isothermal titration calorimetry (ITC), X-ray crystallography, molecular dynamics (MD) simulations, and nuclear magnetic resonance (NMR) spectroscopy have limitations in revealing these molecular interactions. Surface plasmon resonance (SPR), an advanced optical biosensor technique, overcomes these limitations. It enables real-time, label-free monitoring of the interaction dynamics between carbohydrates and proteins through a continuous flow over a chip surface. In this study, we utilized SPR-based techniques to explore the interaction of capsular polysaccharides (CPS) of Klebsiella pneumoniae and the enzyme KpACE (K. pneumoniae acetylated capsule esterase). Our SPR-based analytical platform has several advantages, including shorter experimental time, a simulated physiological state, and minimal sample requirements for investigating carbohydrate–protein interactions. This approach expands the applicability scope of SPR technology and provides a valuable tool for a wide range of research. By using SPR, we successfully verified that KpACE acts on the acetyl groups of CPS, demonstrating its enzymatic activity, which is crucial for understanding the pathogenic mechanism of K. pneumoniae and developing potential antibacterial drugs.